Study, Survey and Analysis for Media Selection - Rinal Harshadkumar Doshi; Rajkumar A. Soni; Bijendra Agrawal; Ravindra L. Naik (Institute of Advanced Engineering and Science, 2012)
This paper is a literature review on practical techniques and rules using PowerPoint, animation, and video effectively for instruction. Instruction may be teaching, training, coaching, tutoring, schooling etc. This paper must be of awareness to mentors and instructional technology staff who support faculty members in the development of instructional media. Main objective of this paper is to identify and select the proper technologies for enhancing a particular pedagogy or learning goal. Choose media that support instructor’s activity.